NAD+ DEPLETION IN THE INTESTINAL EPITHELIUM RESULTS IN MITOCHONDRIAL DYSFUNCTION AND INFLUENCES THE PATHOGENESIS OF EXPERIMENTAL COLITIS. (26th January 2023) - Novak, Elizabeth; Crawford, Erin; Mentrup, Heather; Fletcher, David; Flanagan, Meredith; Schneider, Corinne; Mollen, Kevin
Abstract: We have previously shown that mitochondrial dysfunction and disruption of mitochondrial biogenesis contribute to the pathogenesis of IBD. Peroxisome Proliferator-activated Receptor–gamma Coactivator 1-alpha (PGC1α) is the primary regulator of mitochondrial biogenesis. In patients with ulcerative colitis (UC) and mice undergoing experimental colitis, the transcript and protein levels of PGC1α are reduced, which is concomitant with a decrease in mitochondrial function, derangement of mitochondrial structure, and an increase in oxidative stress. Further, mice lacking PGC1α in the intestinal epithelium develop severe disease during acute and chronic colitis models. PGC1α is primarily activated via deacetylation by the nicotinamide adenine dinucleotide (NAD + )-dependent Sirtuin 1 (SIRT1). Thus, we hypothesized that decreased NAD + in the intestinal epithelium during inflammation renders SIRT1 unable to activate PGC1α, resulting in decreased mitochondrial biogenesis and subsequent mitochondrial dysfunction. Here, we show that levels of deacetylated PGC1α (active) are decreased within the intestinal epithelium of patients with UC (n=4), implying that Sirt1 may be inactivated within diseased tissue. We also found a decrease in the intestional NAD + levels in UC patients (n=10; p<0.001)). Similar to findings in humans, we show that not only are the levels of deacetylated PGC1α (active) decreased within the intestinal epithelium during murine models of DSS colitis (n=10; p<0.001) and infectious ( Citrobacter rodentium -induced) colitis (n=10; p<0.001), but both the transcript and protein levels of Sirt1 are also decreased in mice undergoing experimental colitis (n=10 per group per model). We further found a decrease in intestinal NAD + levels in colitic mice (n=8; p<0.0001). Although we found no significant decrease in the mRNA levels of NAD + -synthesizing enzymes in diseased intestinal tissue (p>0.05), there was a 1.5-fold increase in the intestinal mRNA levels of the NAD + -consuming DNA-repair enzyme Poly(ADP-ribose) polymerase-1 (PARP1) in mice undergoing experimental colitis (n=8; p<0.001), as well as a dramatic increase in the enzymatic activity of PARP1 in DSS-subjected intestinal tissue relative to controls. Treatment of mice undergoing experimental colitis with an NAD + precursor [nicotinamide riboside (NR), 500 mg/kg/day] decreased the severity of colitis (n=10; p<0.001), restored mitochondrial function (p<0.001), and increased active PGC1α levels (p<0.05). NR treatment did not benefit villincre; PGC fl /fl mice (mice that lack PGC1α specifically in the intestinal epithelium; n=10; p>0.05) undergoing experimental colitis, suggesting that the therapeutic effects of NR require active PGC1α. Thus, future therapeutic approaches targeting the activity of PGC1α, and in turn mitochondrial health, may complement the treatment for IBD and improve outcomes in patients.